Corrigendum to “Association between body condition profiles, milk production, and reproduction performance in Holstein and Normande cows” (J. Dairy Sci. 107:11621–11638) - C. Dezetter; F. Bidan; L. Delaby; F. Blanc; S. Freret; N. Bedere (Journal of Dairy Science)
ABSTRACT: Body condition dynamics are known to affect the different steps of reproduction in cattle (cyclicity, estrus expression, fertilization, embryo development). This has led to a widespread idea that there is an ideal-target optimal body condition, but no clear profile has yet been identified. Here we investigated the relationships between BCS profiles and reproductive performance in dairy cows. Data were from Holstein or Normande herds in 6 French experimental farms. In the Holstein breed, we discriminated 4 BCS profiles based on combining BCS at calving (Low indicates BCS ∼2.6 points at calving; High indicates BCS ∼3.3 points at calving) with BCS loss after calving (Moderate [M] indicates BCS loss of ≤1.0 points at calving; Severe [S] indicates BCS loss of >1.0 points at calving). The Low-S profile mostly included multiparous cows with higher milk yield and lower reproductive performance than cows in the 3 other profiles. Low-S cows that experienced abnormal ovarian activity had lower reproductive performance than their profile-mates. Moreover, 67% of Low-S cows kept the same profile at the following lactation. The High-M profile mostly included primiparous cows with lower milk yield and higher reproductive performance than cows in other profiles. In High-M cows, higher milk yields correlated with higher risk of failure to calf on first insemination. Moreover, 38% of High-M cows kept the same profile at the following lactation, and none changed to Low-S. The other 2 BCS profiles (Low-M and High-S) were intermediate in terms of milk yield and reproductive performance. In Normande, we discriminated 3 BCS profiles based on combining BCS at calving (Low: ∼2.6 points; High: ∼3.5 points) with BCS loss after calving (Flat [F]: flat with no loss; M: ∼0.5 points; or S: ∼1.0 point). The Low-M and High-S profiles included cows with similar performance, even though High-S-profile cows showed better but not significantly different milk yield and reproduction performance. The High-F profile included cows that were more likely to experience abnormal ovarian activity and fail at first insemination than cows in other profiles. More than 50% of Normande cows with 2 successive lactations kept in the same BCS profile at the next lactation. Even though a low BCS at calving combined with severe BCS loss (more than 1 point) after calving was found to increase reproductive failure, there was no evidence of an optimal BCS profile for reproduction in dairy cows, and reproductive success or failure is multifactorial.